Leveraging Collaborative Project-Based Learning to Encourage Speaking Proficiency in EFL classroom: A Case Study in Engineering Department - BUTARBUTAR, Ranta; MONIKA, Santy; LEBA, Seli Marlina Radja (Research and Innovation in Applied Linguistics, 2023)
The study aims to explore students' perspectives on the implementation of collaborative project-based learning (CPBL) in the Engineering Department as a means to enhance their understanding of the subject matter and develop problem-solving abilities. A quasi-experimental design was employed, and data was collected through a semi-structured questionnaire. The results indicate that CPBL has the potential to improve students' speaking and presentation skills in various aspects, including grammar, discourse competence, sociolinguistics, strategic competence, fluency, accuracy, and presentation skills. The study also recommends further investigation into computer-mediated communication within group projects and suggests incorporating controlled and energizing task speaking during comparison evaluations to foster reflective thinking among both teachers and students. In summary, this research highlights the positive impact of CPBL on language and presentation skills within the Engineering Department, emphasizing its potential benefits for student learning.